The Pathogenesis of Liver Cirrhosis - Nur Aifiah Binti Ibrahim (INHEALTH : INDONESIAN HEALTH JOURNAL, 2025)
Bile is the final product in the liver digestion system. It is a highly toxic substance called a carcinogen produced after the consumption of alcohol. The esophagus varices occur by the burning sensation from the drop of ether within the drink. Any drinkable beverages will undergo the metabolism for breaking down by the liver. Chronic alcohol consumption intoxicates the bloodstream with harmful substances in the coating process of the scarring tissue covering the liver surfactant. Fat globules and other oxidative stress have increased the bleeding site and worsened the skin condition of the liver. The secretion of bile salts in a regulated number will break down the fat particles from forming a getaway for the gallstones. Atheroma plaque is another condition that enlarges a connective tissue to make it smaller for liver cells to regenerate into its original form.